A mechanistic study of sulphur, nitrogen and oxygen donor bidentate ligand interactions on the rhenium (I) tricarbonyl core - Nkoe, Pheello Isaac (University of the Free State, 2015)
The nuclear properties of rhenium (186/188Re) and technetium (99mTc) are used for their application as diagnostic and therapeutic radiopharmaceuticals. Researchers have shown a significant interest in rhenium and technetium tricarbonyl complexes of the form fac-[M(CO)3X(L,L’-Bid)]n where M = Tc(I) or Re(I), X = entering monodentate ligand and L-L’-Bid = different donor atom bidentate ligands, as potential diagnostic and therapeutic radiopharmaceuticals. These fac-[M(CO)3X(L,L’-Bid)]n type complexes are prepared from the starting synthons fac-[M(CO)3(Br3)]2- and fac-[M(CO)3(H2O)3]+ that was initially prepared by Alberto et al. in 1999. This starting synthon is a favourite all around for the synthesis of potential radiopharmaceuticals due to the easy preparation and the stability of fac-[M(CO)3(H2O)3]+ in aqueous solution in the pH range of 2 - 12 for several hours. The carbonyl ligands are tightly coordinated to the metal and form the stable fac-[M(CO)3]+ core. The three bromido or water ligands can be easily substituted by different functional groups such as thioethers, thiols, phosphines and amines. The aim of this study was to investigate the ability of the chosen donor atom N,O; S,S’; S,O bidentate and S,S’S” tridentate ligands to coordinate to the fac-[Re(CO)3]+ core. The results were compared to previous studies reported on N,O and O,O’ bidentate ligand systems to observe the variation in coordination behaviours. The chosen ligands include: 5-phenylazo-8-hydroxyquinoline, 5-(m-Tol)azo-8-hydroxyquinoline, 5-(2,3- diMephenyl)azo-8-hydroxyquinoline, 5-(2,6-diMe phenyl)azo-8-hydroxyquinoline, 5- (3,4-diMe phenyl)azo-8-hydroxyquinoline, methyl benzo[b]thiophene-2-carboxylate, benzothiophene-2-methanol, 2-mercaptophenol, 2-methoxythiophenol, 5-bromo-2,2`- bithiophene, 2,2′-bithiophene-5-carboxylic acid, benzene-1,2-dithiol, toluene-3,4- dithiol, and 2,2`-thiodiethanethiol. The synthesis of the complexes are described in Chapter 4 and characterized by IR, UV/Vis, NMR (1H and 13C) and elemental analysis. The following crystal structures were obtained fac-[Re2(CO)6(TS)(Py)] (1), fac-[Re2(CO)6PPh3(BSOPhC)2(Py)] (2), fac- [NEt4][Re2(CO)6(BSOPhC)3] (3) and fac-[Re2(CO)6(m-TolBSPh)2] (4). All four of the structures has four molecules per unit cell (Z = 4). (1) and (4) crystallized in the P1̅ space group while (2) and (3) crystallized in a monoclinic space group. In all four these structures the ligands form sulphur bridges between two rhenium (I) centres. The Re-CO bond distances of all the crystal structures range from 1.88(3) Å to 1.95(10) Å and the Re-S bond distances vary from 2.44(2) Å to 2.56(7) Å. (2) has a Re-P bond distance of 2.51(12) Å and a Re-N bond distance of 2.24(4) Å. The S-Re-S bond angles range from 76.26(3) ° to 94.99(8) ° and the Re-S-Re bond angles from 87.28(9) ° to 100.60(4) ° with the non-bonding rhenium to rhenium distances of 3.796(8) Å for (1), 3.845(10) Å for (2), 3.488(10) Å for (3) and 3.654(16) Å for (4). The non-bonding Re…Re distances are directly proportional to the Re-S-Re angles and follow the following trend: (3) < (4) < (1) < (2). A fairly good comparison could be made between previously reported structures with S,S’; S,O; N,O and O,O’-bidentate ligands coordinated to the fac-[Re(CO)3]+ core. The structure of (4) has been reported before and a very good correlation is found between this structure and the reported structure. After an in depth study it was confirmed that the structures of all the compounds with S,O; S,S’ and S,S’,S’’ ligands have to be analysed by single crystal XRD or at least a quantitative NMR study. For one ligand system (BSOPhC), two different structures were obtained with only a slight change in the synthetic procedure. It is not that easy to determine and speculate the bonding modes of these type of ligands. Therefore a complete crystallographic study will form part of the future work for this project. Excellent results were obtained for anti-mitochondrial activity screening for five compounds. The next step will be to improve the solubility of these complexes, especially in water as solvent; this illustrates the possible use of these compounds as potential radiopharmaceuticals.

Die kern eienskappe van renium (186/188Re) en tegnesium (99mTc) word gebruik vir hulle toepassing in diagnostiese en terapeutiese radiofarmasie. Navorsers het reeds beduidende belangstelling getoon in renium en tegnesium trikarboniel komplekse van die vorm fas-[M(CO)3X(L,L’-Bid)]n, waar M = Tc(I) of Re(I), X = inkomende monodentate ligand en L-L’-Bid = verskillende skenkeratoom bidentate ligande, vir toepassing as potensiële diagnostiese en terapeutiese radiofarmaseutiese middels. Hierdie fas-[M(CO)3X(L,L’-Bid)]n tipe komplekse is voorberei vanaf fas-[M(CO)3(Br3)]2- en fas-[M(CO)3(H2O)3]+ wat aanvanklik deur Alberto et al. in 1999 berei is. Hierdie begin sinton is ŉ algemene gunsteling vir die sintese van potensiële radiofarmaseutiese middels danksy die maklike bereiding en stabiliteit van fas- [M(CO)3(H2O)3]+ in wateroplossing in ŉ pH reeks van 2 tot 12 vir verskeie ure. Die karboniel ligande is stewig aan die metaal gekoördineer en vorm die stabiele fas- [M(CO)3]+ kern. Die drie bromido of water ligande kan maklik deur verskillende funksionele groepe soos tioësters, tiole, fosfiene en amiene gesubstitueer word. Die doel van hierdie studie was om die vermoë van die gekose skenkeratoom N,O; S,S’; S,O bidentate en S,S’S” tridentate ligande aan die fas-[Re(CO)3]+ kern te koördineer te ondersoek. Die resultate is met vorige studies rakende N,O en O,O’ bidentate ligandstelsels vergelyk ten einde die variasie in koördinasiegedrag waar te neem. Die gekose ligande sluit in: 5-fenielaso-8-hidroksiekinolien, 5-(m-Tol)aso-8- hidroksiekinolien, 5-(2,3-diMe-feniel)aso-8-hidroksiekinolien, 5-(2,6-diMe-feniel)aso-8- hidroksiekinolien, 5-(3,4-diMe-feniel)aso-8-hidroksiekinolien, metiel benso[b]tiofeen-2- karboksilaat, bensotiofeen-2-metanol, 2-merkaptofenol, 2-metoksietiofenol (BSOFCH), 5-bromo-2,2`-bitiofeen, 2,2′-bitiofeen-5-karboksielsuur, benseen-1,2-ditiol, tolueen-3,4-ditiol (m-TolBSFH2) en 2,2`-tiodietaantiol (TSH2). Die sintese van die komplekse word in Hoofstuk 4 beskryf en is gekarakteriseer deur IR, UV/Vis, KMR (1H en 13C) en elementanalise. Die volgende kristalstrukture is verkry: fas-[Re2(CO)6(TS)(Py)] (1), fas-[Re2(CO)6PF3(BSOFC)2(Py)] (2), fas- [NEt4][Re2(CO)6(BSOFC)3] (3) en fas-[Re2(CO)6(m-TolBSF)2] (4). Al vier van die strukture het vier molekule per eenheidsel (Z = 4). (1) en (4) kristalliseer in die P1̅ ruimtegroep terwyl (2) en (3) in ŉ monokliniese kristalstelsel kristalliseer. In al vier van hierdie strukture vorm die ligande swael brûe tussen twee renium (I) kerne. Die Re-CO bindingsafstande van al die kristalstrukture wissel van 1.88(3) Å tot 1.95(10) Å en die Re-S bindingsafstande wissel van 2.44(2) Å tot 2.56(7) Å. (2) het ŉ Re-P bindingsafstand van 2.51(12) Å en ŉ Re-N bindingsafstand van 2.24(4) Å. Die S-Re-S bindingshoeke wissel vanaf 76.26(3) ° na 94.99(8) ° en die Re-S-Re bindingshoeke tussen 87.28(9) ° en 100.60(4) ° met die ongebonde renium na renium afstande van 3.796(8) Å vir (1), 3.845(10) Å vir (2), 3.488(10) Å vir (3) en 3.654(16) Å vir (4). Die ongebonde Re…Re afstande is direk eweredig aan die Re-S-Re hoeke en volg die volgende tendens: (3) < (4) < (1) < (2). ŉ Betreklik goeie vergelyking kon getref word tussen voorheen gemelde strukture met S,S’; S,O; N,O en O,O’ bidentate ligande wat aan die fas-[Re(CO)3]+ kern gekoördineer is. Die struktuur van (4) is voorheen gerapporteer en ŉ baie goeie ooreenkoms tussen hierdie struktuur en die gerapporteerde struktuur is gevind. Na ŉ deeglike studie is dit bevestig dat die strukture van alle verbindings met S,O; S,S’ en S,S’,S’’ ligande deur middel van enkelkristal X-straal diffraksie of ten minste ŉ kwantitatiewe KMR studie geanaliseer moet word. Vir een ligandstelsel (BSOFC) is twee verskillende strukture verkry met slegs ŉ geringe verandering in die sintetiese prosedure. Dit is nie maklik om die bindingsmodusse van hierdie tipe ligande vas te stel en daaroor te spekuleer nie, daarom vorm ŉ volledige kristallografiese studie deel van die toekomstige doelwitte vir hierdie projek. Uitstekende resultate is vir die anti-mitokondriese aktiwiteitsifting vir vyf verbindings verkry. Die volgende stap is die verbetering van die oplosbaarheid van hierdie komplekse, veral in water as oplosmiddel; dit illustreer die moontlike gebruik van hierdie verbindings as radiofarmaseutiese middels.
Dissertation (M.Sc. (Chemistry))--University of the Free State, 2015
Keywords: Radiopharmaceuticals